Beyond Survival: Lessons From a Research Journey in Critical Care Recovery Science. - Boehm, Leanne M. (American Journal of Critical Care, 2026)
My research journey began while caring for critically ill patients and questioning what happens after they leave the intensive care unit (ICU). This curiosity evolved into a systematic program of research on post–intensive care syndrome and evidence-based recovery interventions that has influenced how nurses approach the transition from critical illness survival to meaningful recovery. The goal of my research has been to eliminate delirium, oversedation, and immobilization in intensive care and to maximize the quality of survivorship for patients and family members after critical illness. I have led investigations into implementation of the ABCDEF bundle (assess, prevent, and manage pain; both spontaneous awakening and spontaneous breathing trials; choice of analgesia and sedation; delirium: assess, prevent, and manage; early mobility; family engagement and empowerment), demonstrating how organizational factors like workload burden, unit leadership, and interprofessional coordination influence implementation adherence and patient outcomes. My work in telemedicine-enhanced follow-up care of patients with post–intensive care syndrome addresses the cognitive, physical, and psychological impairments that affect more than half of ICU survivors. Work implementing ICU diary and peer support programs has shown how evidence-based interventions can support patients and family members when barriers to implementation are systematically addressed. My efforts embody interdisciplinary collaboration, integrating nursing science with implementation science, health services research, and clinical psychology. My journey illustrates how bedside observations, when coupled with rigorous inquiry, collaborative partnerships, and intentionality to let patient and family voices reshape thinking, can drive meaningful contributions that improve outcomes for patients and families beyond survival.